2014
DOI: 10.1002/glia.22665
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 beta enhances endocytosis of glial glutamate transporters in the spinal dorsal horn through activating protein kinase C

Abstract: Excessive activation of glutamate receptors in spinal dorsal horn neurons is a key mechanism leading to abnormal neuronal activation in pathological pain conditions. Previous studies have shown that activation of glutamate receptors in the spinal dorsal horn is enhanced by impaired glial glutamate transporter functions and pro-inflammatory cytokines including interleukin-1 beta (IL-1β). In this study, we for the first time revealed that spinal glial glutamate transporter activities in the neuropathic animals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 78 publications
1
92
0
Order By: Relevance
“…The size of GTCs reflects the amount of transported glutamate, which has been widely used as an effective tool to study the function of glial GTs. 14,36,50 We recently reported that mice with pSNL had lower amplitudes of GTCs. 14 After recording baseline GTCs in spinal slices taken from neuropathic GFP-GFAP mice, we perfused the AMPK activator (AICAR, concentration in the bath: 10 μM) into the recording chamber and recorded GTCs again.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The size of GTCs reflects the amount of transported glutamate, which has been widely used as an effective tool to study the function of glial GTs. 14,36,50 We recently reported that mice with pSNL had lower amplitudes of GTCs. 14 After recording baseline GTCs in spinal slices taken from neuropathic GFP-GFAP mice, we perfused the AMPK activator (AICAR, concentration in the bath: 10 μM) into the recording chamber and recorded GTCs again.…”
Section: Resultsmentioning
confidence: 94%
“…For measuring protein expression in the plasma membrane and cytosol in rat spinal slices, spinal slices of the spinal L4 to L5 segment were obtained as previously described. 14 Spinal slices were incubated with plain artificial cerebrospinal fluid (aCSF), aCSF plus IL-1β (10 ng/mL), or aCSF plus IL-1β (10 ng/mL) and AICAR (10 μM) bubbled with 95% O 2 and 5% CO 2 at 35°C for 15 min. The dorsal halves of the spinal slices were quickly frozen in liquid nitrogen and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations